(untitled) (Eurasian Journal of Philology Science and Education, 2015)
This article presents izafats of II type and combinations of izafat that are stated in the dictionary by Abylgazy bakhadur khan under the name «Түркі шежіресінің тезаурус сөздігі». In the branch of language morphology there is a definition for the structure of the combination of izafat. This concept was developed in arab language and comes from «Al- idafatu», the direct translation means additional. The meaning of Izafat II comes from the Turkic times and the specific value is divided into several groups. In this article it is stated an opinion of well-known professor Talgat Sairanbaev on the subject about Izafat and an effect in the sentence of three types of Izafat. In the article also, stated the other scientists’ ideas on izafat. In the combinations of izafat II and words in this combinations there is strict word order and no possibility to add another words. This type of izafat comes from the ancient types of word combinations. And this example is met in the written monuments of ancient Turkic languages and in all modern Turkic languages